700 keV Au ions beam effect on the structural, optical and photovoltaic properties of MAPbI3 solar cells. Issue 5 (1st March 2023) - Khan, M.I.; Aldulmani, Sharah A.; Nadeem, M. Arslan; Hussain, Saddam; Subhani, Waqas Siddique; Saleem, Muhammad; Fatima, Mahvish; Mehmood, Bilal; BaQais, Amal; Alissa, Siham A.
Abstract: Organic-inorganic halide perovskites with enhanced energy orientation in optoelectronic devices will also have a huge impact on solar cell performance because of their low manufacturing cost and long lifetime. The pure methylammonium lead iodide (CH3 NH3 PbI3 or MAPbI3 ) films are coated on FTO-glass substrates by sol-gel spin coating technique. Gold (Au) ions with fluence rates of 2x10 14 and 4x10 14 ions/cm 2 are implanted on these films to enhance their structural, morphological and photovoltaic performance. The cubic crystal structure is present in all of the films. The grain size of the film implanted with 2x10 14 ions/cm 2 is large. According to AFM and FESEM images, the grains in the pure material are tightly packed and connected to one another with distinct grain boundaries, but when Au ions are implanted, the size of the grains increases. The optical characteristics like dielectric constant, bandgap, refractive index, and extinction coefficients are measured using the UV–Vis spectrometry technique. All films have direct band gap and the films irradiated with 2x10 14 ions/cm 2 has low band gap energy (1.52 eV). The solar cells of these films are manufactured. Each cell performs well overall. The Mott Schottky analysis, charge transfer resistance, and space charge limited current calculations all offer strong support for the excellent efficiencies of such films. The cell fabricated with 2x10 14 ions/cm 2 implanted Au ions has large a short-circuit current density of 10.57 mA/cm 2, a Fill-Factor of 0.82, open circuit voltage of 1.03 V, and an efficiency of 8.94%.